Pengaruh Aplikasi Pupuk Hayati Mikroba Pelarut Fosfat dalam Meningkatkan Kandungan P tanah , Pertumbuhan dan Hasil Jagung pada Ultisols - Betty Natalie Fitriatin; Aristyo Rahardiyan; Tien Turmuktini (Soilrens, 2016)
Marginal soils have problems of low availability of nutrients, especially phosphorus. Phosphate solubilizing microbes can produce organic acid that dissolve P in the soil. Futhermore, the PSM also produce extracellular enzymes asa phosphatase that catalyze mineralization of organic P become inorganic P. Phosphate solubilizing bacteria (Pseudomonas mallei and Pseudomonas cepacea) and phosphate solubilizing fungi (Penicillium sp. and Aspergillus sp) is selected based on the ability of dissolving P and the production of growth regulators. Research at this stage aims to determine the biological fertilizer application techniques (PSB and PSF) as well as different types of P fertilizers to improve soil P available, growth and yield of maize. Field experiment on Ultisol Jatinangor implemented using a randomized block design (RBD) to test how applications PSM plus (giving 1, 2 and 3 applications) as well as the type of fertilizer P (SP-36 and rock phosphate). The results showed that the application of PSM can improve soil P-available growth and yield of maize. Application of PSM biological fertilizer could reduce the need for fertilizer P by 50%. PSM application once the application (early planting) with SP-36 dose 50% can increase content of soil P (P-available), and yield of maize on Ultisols.Keywords : maize, phosphate solubilizing microbes, Ultisols